ANALISA PERAMALAN PRODUK PALET KAYU DI CV. BAROKAH UTAMA - Josenda, Rade; Asmarawati, Citra Indah (Computer Science and Industrial Engineering, 2021)
Forecasting is a method of predicting the future based on a systematic analysis of past and current facts for a certain period of time. To minimize the excess and shortage of production, as well as shortage of raw materials, forecasting is needed. There are a variety of forecasting methods available, each with varying degrees of accuracy and error. The lowest MAD, MSE, and MAPE error values produce the best forecasting results. The goal of this study is to find the best forecasting approach for CV. Barokah Utama. Moving Average, Exponential Smoothing, Holt Exponential Smoothing, Linear Regression, and Trend Projection are the methods used. Based on the MAD, MSE, and MAD values, the Moving Average method with a value of n = 3 was found to be the most suitable method with the lowest error value.